INCLUSIVE ENTREPRENEURSHIP EDUCATION: EFFORTS TO FOSTER ENTREPRENEURIAL SPIRIT AMONG VULNERABLE AND MARGINALISED GROUPS - Hanif, Muh.; Suherlan (Technopreneurship and Educational Development Review (TENDER), 2025)
This study aims to examine inclusive entrepreneurship education as a strategy for fostering entrepreneurial spirit among vulnerable and marginalised groups, such as female heads of households, people with disabilities, young unemployed people, and urban poor communities. This study employs a qualitative approach using a literature review method, analysing 23 carefully selected scientific articles from a total of 50 initial sources obtained through Google Scholar and other credible websites during the period 1984–2025. The analysis results indicate that contextual, participatory, and community-based entrepreneurship education can enhance the competencies, motivation, and economic opportunities of the target groups. This study also integrates several theoretical frameworks, such as the Capability Approach, Transformative Learning, and Inclusive Innovation, to explain how education can promote structural empowerment and economic independence. Additionally, case studies from community-based programmes in Indonesia provide concrete evidence of the importance of cross-sectoral collaboration in supporting entrepreneurial inclusion. This research concludes that inclusive entrepreneurship education has great potential to drive social transformation and poverty alleviation, despite facing structural and institutional challenges.